1983
DOI: 10.18785/grr.07supp.02
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of the Biology of the Red Drum, Sciaenops ocellatus, in Mississippi

Abstract: Several hundred specimens of the red drum from Mississippi were critically assessed. Regression equations for standard-length (SL) versus total-length differed between males and females and between small and large members of the same sex. A single regression line represented the weight-SL relationship for males with females. For condition coefficients to be helpful, fish had to be grouped at least by sex, season, and length or stage of maturity. By 12 months of age, most fish were about 30 to 32 cm SL and thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 32 publications
(16 reference statements)
4
42
1
Order By: Relevance
“…Observed fidelity of subadult and adult red drum to natal sites may be due to localized retention or limited inter-estuary movement, which is common for species in the family Sciaenidae, including red drum (Baker & Matlock 1993, Murphy et al 1998, Adams & Tremain 2000. Mark-recapture studies on red drum in the Gulf of Mexico and along the eastern seaboard of the US have shown that the majority of individuals originated from nurseries within the same estuary or region as the capture location (Osborn et al 1982, Overstreet 1983, Nicholson & Jordan 1994. Moreover, Tremain et al (2004) observed high site fidelity of red drum from a no-take zone in Florida, with over 95% of the recaptures occurring at the tagging location within the reserve.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Observed fidelity of subadult and adult red drum to natal sites may be due to localized retention or limited inter-estuary movement, which is common for species in the family Sciaenidae, including red drum (Baker & Matlock 1993, Murphy et al 1998, Adams & Tremain 2000. Mark-recapture studies on red drum in the Gulf of Mexico and along the eastern seaboard of the US have shown that the majority of individuals originated from nurseries within the same estuary or region as the capture location (Osborn et al 1982, Overstreet 1983, Nicholson & Jordan 1994. Moreover, Tremain et al (2004) observed high site fidelity of red drum from a no-take zone in Florida, with over 95% of the recaptures occurring at the tagging location within the reserve.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, lower survival of migrants originating from outside nurseries may also explain the lower contribution rates and/or mixing of individuals from other regions. Although the dispersal potential of adult red drum is assumed to be high (Overstreet 1983), additional information on movement away from estuarine nurseries is needed to confirm that homing, rather than retention, was the primary behavior responsible for red drum being in tidal passes or coastal environments nearest to their putative nursery. The combined effects of localized retention and natal homing explain findings from tagging, genetics and otolith chemistry, but the degree to which each behavior is responsible for observed patterns remains unresolved.…”
Section: Discussionmentioning
confidence: 99%
“…In the Gulf of Mexico, S. tenuis has been reported by Bere (1936), Heegaard (1966), and Overstreet (1983) from banded drum, Larimus fasciatus Holbrook, 1855, black drum, and red drum, respectively. Lesions and pathologic responses to sea louse infection were described in several other teleosts (e.g.…”
Section: Introductionmentioning
confidence: 92%
“…Spawning red drum can be found in both open and nearshore waters in the Gulf of Mexico and tend to spawn near shorelines during late summer and fall (Tables 9.27 and 9.28). There is little evidence of seasonal migration of red drum, and they have been found in rivers and tidal creeks during Bass and Avault (1975) Common predators of juveniles Amberjack, large piscivorous fishes, sharks, and birds; typically not normal part of diet of any common estuarine predator Overstreet (1983), Porch (2000) Common predators of adults Sharks; not a normal part of the diet of any common estuarine predator the winter. Tides and water temperatures influence daily movement from shallow to deepwaters.…”
Section: Key Life-history Processes and Ecologymentioning
confidence: 99%
“…Tagging studies suggest that juvenile red drum have limited dispersal but that adults can travel considerable distances in the Gulf of Mexico (Osburn et al 1982;Overstreet 1983). Metapopulation structure may exist for the red drum in the Gulf of Mexico, and despite the likely complex spatial structure of the stock, red drum in the Gulf of Mexico is considered as a single stock, which implicitly assumes no spatial heterogeneity in the Gulf of Mexico red drum population.…”
Section: Designated Essential Fish Habitatmentioning
confidence: 99%